Optimization of SatSamapta Performance of Demak District Police in Handling Community Issues to Realize a Predictive Indonesian National Police - Simbolon, Daud Jhon Piter (Advances in Police Science Research Journal, 2024)
This research aims to optimize the performance of the Satsamapta task force of Demak District Police in handling community diseases in order to realize a predictive Indonesian National Police (Polri). This research was conducted using a qualitative approach with a case study method. Data were collected through in-depth interviews and participatory observation with members of the Satsamapta of Demak District Police, as well as related documents. Data analysis was performed using reduction, presentation, and verification techniques. The results show that the Satsamapta of Demak District Police has successfully performed their duties in handling community diseases, but there are still several obstacles that need to be addressed. Several factors that affect the performance of Satsamapta include the lack of support from other parties, lack of experience in handling complex cases, and limited facilities and infrastructure. To optimize the performance of Satsamapta, this research recommends several strategic actions, such as increasing coordination among related parties, training and developing the capabilities of Satsamapta members, and improving facilities and infrastructure that support the task force's duties. It is hoped that with the implementation of these recommendations, the Sasamapta of Demak District Police can be more effective in handling community diseases, and Polri can become a more predictive institution in fulfilling the needs of the community.